Nilai Edukatif dalam Novel Children Of Heaven Karya Enang Rokajat Asura untuk Membangun Literasi Kritis Serta Relevansinya Sebagai Materi Ajar Bahasa Indonesia SMP Kelas VII - Elisabet Mangera; Bambang Yulianto; Heny Subandiyah; Tensoe Tjahjono (Peneliti.net, 2021)
The purpose of this study was to describe the educational value contained in the novel Children of Heaven by Enang Rokajat Asura. The type of research used is a qualitative type of literature. Research data sourced from the novel Children of Heaven. Furthermore, the data were analyzed using an objective approach. The method used in this research is content analysis using reading and note-taking techniques. The results showed that the Children of Heaven novel contains educational values ​​(1) the value of love, (2) the value of dependability, (3) the value of simplicity, (4) the value of cooperation, (5) the value of happiness. The results of this study are expected to increase knowledge about the educative values ​​contained in the novel so that it can foster critical literacy and as the relevance of Indonesian language teaching materials for seventh grade junior high schools.